A spontaneous leptin receptor point mutation causes obesity and differentially affects leptin signaling in hypothalamic nuclei resulting in metabolic dysfunctions distinct from db/db mice - Piattini, Federica (Mol Metab, 2019)
OBJECTIVE: Leptin (Lep) plays a crucial role in controlling food intake and energy expenditure. Defective Lep/LepRb-signaling leads to fat accumulation, massive obesity, and the development of diabetes. We serendipitously noticed spontaneous development of obesity similar to LepR-deficient (db/db) mice in offspring from a C57BL/6J breeding and transmittance of the phenotype in a Mendelian manner. Candidate gene sequencing revealed a spontaneous point mutation in the LepRb gene. We investigated leptin responsiveness, leptin receptor signaling and metabolic phenotype of this novel LepRb mutant mouse variant. METHODS: Overexpression and functional tests of the mutant LepRb in 3T3 cells. Measurement of leptin responsiveness in hypothalamic nuclei, glucose tolerance, food uptake and energy expenditure in the mutant mice. RESULTS: The mutation results in the exchange of a glycine for serine (G506S) and introduces an alternative splice acceptor which, when used, encodes for a protein with a 40aa deletion that is retained in the cytoplasm. LepRb signaling was abrogated in the hypothalamic ventromedial nucleus (VMN) and dorsomedial nucleus (DMN), but only partially reduced in the hypothalamic arcuate nucleus (ARC) of LepRb(G506S/G506S) mice, most likely due to differential splicing in neurons located in the respective regions of the hypothalamus. Extensive metabolic characterization of these mice revealed interesting differences in the control of food intake, glucose tolerance, energy expenditure, and fat accumulation in LepRb(G506S/G506S) compared with LepRb-deficient db/db mice. CONCLUSIONS: This study provides further insight into differences of the leptin responsiveness in VMN, DMN, and ARC and its metabolic consequences.